GLOBALIZATION OF EDUCATION: NEW RESPONSIBILITIES OF UNIVERSITY AND TEACHERS FOR SUSTAINABLE DEVELOPMENT - Natalia V. Tikhomirova (Статистика и экономика, 2016)
Over the centuries, the role of universities has remained unchanged, they were aheart of production and reproduction ofknowledge and skilled labor force. Butin the second half of the 20th century,external media environment has changeddramatically. The information society,knowledge-based society, smart society began to emerge. Rapidly changing technologies are changing the nature of theeducational process that makes universities to respond quickly to the challenges ofmodern society. Conventional universities found themselves facing new challengesand to teachers opened a completely newrange of possibilities.